The Effect of the Project-Based Learning Model on Students' Learning Outcomes and Learning Activities - Sofa, Mahira Maya; Sudrajat, Ajat (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study was motivated by the low level of students’ learning outcomes and learning activities on electrolyte and non-electrolyte solution material. The study aimed to examine the effect of the Project Based Learning (PjBL) model on students’ learning outcomes, to describe students’ learning activities after its implementation, and to determine the relationship between learning activities and learning outcomes. This research employed a quasi-experimental method with a pretest-posttest control group design. The sample consisted of 55 students selected through cluster random sampling, divided into an experimental class taught using the PjBL model and a control class taught using the Direct Instruction model. The data were collected through learning outcome tests and observation sheets of students’ learning activities, then analyzed using N-gain, correlation analysis, and an independent sample t-test. The results showed that the experimental class achieved a higher increase in learning outcomes (N-gain 0.75, high category) compared to the control class (N-gain 0.68, medium category). The hypothesis test indicated a statistically significant difference between the two groups (p < 0.05). In addition, students’ learning activities in the experimental class were categorized as high (86.73%). Correlation analysis revealed a positive and significant relationship between learning activities and learning outcomes, with a contribution of 38.0%. In conclusion, the Project Based Learning model significantly improves students’ learning outcomes and positively contributes to students’ learning activities on electrolyte and non-electrolyte solution material.